2017
DOI: 10.3847/1538-4357/aa6840
|View full text |Cite
|
Sign up to set email alerts
|

Casting the Coronal Magnetic Field Reconstruction Tools in 3D Using the MHD Bifrost Model

Abstract: Quantifying coronal magnetic field remains a central problem in solar physics. Nowadays the coronal magnetic field is often modelled using nonlinear force-free field (NLFFF) reconstructions, whose accuracy has not yet been comprehensively assessed. Here we perform a detailed casting of the NLFFF reconstruction tools, such as π-disambiguation, photospheric field preprocessing, and volume reconstruction methods using a 3D snapshot of the publicly available fullfledged radiative MHD model. Specifically, from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 51 publications
(68 reference statements)
1
27
0
1
Order By: Relevance
“…These magnetograms were employed as the bottom boundary conditions to perform NLFFF reconstruction of the coronal magnetic field. Specifically, we employed two different versions of the optimization method Fleishman et al (2017) found that existing methods of the photospheric magnetic boundary condition preprocessing, proposed to remove the forced component of the magnetic field, in fact result in a corrupted height scale, and do not improve quality of the reconstruction. Therefore, we did not apply any preprocessing, but used the bottom boundary condition as is.…”
Section: Nlfff Reconstruction Of Coronal Magnetic Fieldmentioning
confidence: 99%
“…These magnetograms were employed as the bottom boundary conditions to perform NLFFF reconstruction of the coronal magnetic field. Specifically, we employed two different versions of the optimization method Fleishman et al (2017) found that existing methods of the photospheric magnetic boundary condition preprocessing, proposed to remove the forced component of the magnetic field, in fact result in a corrupted height scale, and do not improve quality of the reconstruction. Therefore, we did not apply any preprocessing, but used the bottom boundary condition as is.…”
Section: Nlfff Reconstruction Of Coronal Magnetic Fieldmentioning
confidence: 99%
“…It supplies the user with a possibility of automated production of 3D magneto-plasma data cube built for a user-defined field of view and spatial resolution. The 3D magnetic model is created by nonlinear force-free field reconstruction (Fleishman et al 2017) initiated with the corresponding photospheric vector magnetogram automatically downloaded from the HMI/SDO site. We employed the GX Simulator for 3D modeling of the flaring loops and computation of the associated electromagnetic emission.…”
Section: Analysis and Modeling Toolsmentioning
confidence: 99%
“…The highresolution chromospheric movie of the flare shows a very complex small-scale (subarcsecond) structure with changing loops, which do not seem to be reproduced by this global lower-resolution NLFFF model and this could be a major contributor to the observed discrepancies. Tests of a nonlinear force-free reconstruction on boundary data from a radiative magneto-hydrodynamic simulation show that the NLFFF model performs poorly in representing the field structure in the chromosphere (Fleishman et al 2017). The low atmosphere is not force-free, and in particular the gas pressure and gravity force are dynamically important.…”
Section: Comparison Of Magnetic Field Changesmentioning
confidence: 99%
“…In summary, for the purpose of reproducing the observed field changes at the photosphere and chromosphere, the force-free field model appears to be inadequate, because a NLFFF reconstruction based on photospheric boundary conditions does not include the physics of the chromosphere (Fleishman et al 2017). A possible next step is a magneto-hydrostatic model (e.g.…”
Section: Comparison Of Magnetic Field Changesmentioning
confidence: 99%